Autorzy:Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Oblicz 4.0 gwiazdek na podstawie 9 opinii

`a)\ (sqrt3+1)^2=` `sqrt3^2+2*sqrt3*1+1^2=`  

`\ \ \ =3+2sqrt3+1=2sqrt3+4` 

`b)\ (sqrt10-2)^2=` `sqrt10^2-2*sqrt10*2+2^2=` 

`\ \ \ =10-4sqrt10+4=` `14-4sqrt10` 

`c)\ (sqrt3-sqrt2)^2=` `sqrt3^2-2*sqrt3*sqrt2+sqrt2^2=` 

`\ \ \ =3-2sqrt(3*2)+2=` `5-2sqrt6` 

`d)\ (sqrt8+sqrt2)^2=sqrt8^2+2*sqrt8*sqrt2+sqrt2^2=` 

`\ \ \ =8+2sqrt(8*2)+2=` `10+2sqrt16=10+2*4=18` 

`e)\ (sqrt5-1)(sqrt5+1)=sqrt5^2-1^2=5-1=4` 

`f)\ (sqrt6+sqrt3)(sqrt6-sqrt3)=sqrt6^2-sqrt3^2=6-3=3`